DA'WAH VISUAL COMMUNICATION DESIGN FROM THE ANIMATED FILM : DA'WAH VISUAL COMMUNICATION DESIGN FROM THE ANIMATED FILM “I'M THE BEST MUSLIM, SEASON 1, EPS. 8” ON YOUTUBE CHANNEL FREE QUR'AN EDUCATION) - Jannah, Raudatul; Fadlilah, Siti Nur (Program Studi Komunikasi Penyiaran Islam STID Mohammad Natsir, 2023)
Research purposes:To find out the da'wah visual communication design from the animated film 'I'm the Best Muslim, season 1' on the Free Qur'an Education YouTube channel. Research Method: Qualitative Descriptive. Research Results: Based on research conducted on 17 captures or stills from the animated film 'I'm The Best Muslim, Season 1, Eps. 8' which was broadcast on the Free Qur'an Education YouTube channel account, through the analysis of Charles Sanders Pierce's semiotic theory, namely triangle meaning, there are 3 elements in it (Icon, Index and Symbol). From all film captures/cuts, the average design refers to a type of image that is a combination of illustration, typography and digital imagine, namely the meaning of the visual design of icons, indexes and symbols is the visual depiction of eyes in the form of hamzah letters, illustrations of characters who have separate bodies or has no neck, a star symbol that is in line with the theme or title of the animated film, the background and characters are orange with the meaning of enthusiasm, energy, cheerfulness and positive vibes, as well as typography in the form of the FQE logo in each capture. Conclusion: The visual communication design produced by the animated film 'I'm the Best Muslim has a design concept that focuses on animated depictions that refer to the laws or rules of drawing according to Islamic law, color. The colors and designs created or displayed in the film are still in the safe category, containing no elements or forms of deviation in visual design, illustrations, typography and color. .